A case for crop wild relative preservation and use in potato - Jansky, S.H.; Dempewolf, Hannes; Camadro, E.L.; Simon, R.; Zimnoch-Guzowska, E.; Bisognin, D.A.; Bonierbale, Merideth W. (Wiley, 2013)
Crop wild relatives (CWR) offer a critical resource to address food security needs by providing genetic diversity for crop improvement, leading to increased plasticity and productivity of farming systems. However, plant breeders typically have not developed systematic or comprehensive strategies for the characterization and use of CWR for cultivar improvement. Potato (Solanum tuberosum L.) provides an excellent case study for the use of CWR germplasm in addressing global food security needs. International cooperation and collaboration are critical to collect, characterize, and use CWR in anticipation of future production needs. Both ex situ and in situ preservation of wild potato species are essential to assure a comprehensive conservation plan. Top priorities include a coordinated inventory of gene bank holdings followed by re‐collection of CWR and new collection where gaps exist. Access to CWR genetic diversity will continue to be critical as breeders face the challenge of developing cultivars that fit into new production systems, especially in response to climate change. With the advent of the genomics era, new visions of germplasm use strategies are emerging. In addition to filling gaps in collections, it will be important to expand efforts to characterize and use potato CWR. A systematic and integrated strategy is needed to evaluate CWR in gene banks for traits to continue breeding progress.